HWWI Commodity Price Index: A technical documentation of the 2023 revision - Michael Berlemann; Marina Eurich; Hennes Meyer (Hamburg Institute of International Economics (HWWI), 2023)
The HWWI Commodity Price Index, which aims at reflecting price developments of raw materials imported by highly industrialized countries, dates back to the 1950s. This paper explains the calculation of the index at the example of its latest revision, which became effective on 1st September 2023. While the index and its subindices are still calculated for OECD and European Momentary Union countries at four different frequencies (annual, monthly, quarterly and daily) for two different currencies (USD, EUR), it now additionally includes index values for several weighting periods (long-term: 2012-2021, pre-crisis: 2017-2019 and crisis years: 2020- 2021), for individual countries and for different perspectives (daily revised, real-time and historical time series). The paper also provides detailed information on the employed methodology and the input data (commodities, import data, prices) used to calculate the weights and the index values. Although the revision is not without effect on the resulting index values, especially throughout the crises periods, the correlation between the initial and the revised index remains very high. – – Der HWWI-Rohstoffpreisindex, der die Preisentwicklung der von hochindustrialisierten Ländern importierten Rohstoffe widerspiegeln soll, geht auf die 1950er Jahre zurück. In diesem Papier wird die Berechnung des Indexes am Beispiel seiner letzten Revision erläutert, die am 1. September 2023 in Kraft trat. Während der Index und seine Teilindizes nach wie vor für die Länder der OECD und der Europäischen Währungsunion in vier verschiedenen Frequenzen (jährlich, monatlich, vierteljährlich und täglich) für zwei verschiedene Währungen (USD, EUR) berechnet werden, enthält er nun zusätzlich Indexwerte für mehrere Gewichtungszeiträume (langfristig: 2012-2021, vor der Krise: 2017-2019 und in den Krisenjahren: 2020-2021), für einzelne Länder und für verschiedene Zeitperspektiven (täglich überarbeitete, Echtzeit- und historische Zeitreihen). Das Papier enthält auch detaillierte Informationen über die angewandte Methodik und die zur Berechnung der Gewichte und der Indexwerte verwendeten Inputdaten (Rohstoffe, Importdaten, Preise). Obwohl die Revision nicht ohne Auswirkungen auf die resultierenden Indexwerte ist, insbesondere in Krisenzeiten, bleibt die Korrelation zwischen dem ursprünglichen und dem revidierten Index sehr hoch.
Keywords: 330